Multidisciplinary approach with botulinum toxin (BTX) and 3D printing stabilization splint in cases of temporomandibular joint osteoarthritis exacerbated by bruxism - Dina Hudiya Nadana; Ismet Danial Nasution; Ricca Chairunnisa (Indonesian Journal of Prosthodontic, 2026)
ABSTRACT: Background: Temporomandibular joint disorder (TMD) is a multifactorial condition involving the masticatory muscles and temporomandibular joint. Temporomandibular joint osteoarthritis (TMJ OA), is a degenerative joint disorder marked by articular surface erosion, crepitus, and joint pain. Parafunctional habits such as bruxism can exacerbate OA by increasing biomechanical load on the TMJ, accelerating joint degeneration, and worsening symptoms. Conservative treatments such as stabilization splints are commonly used in TMD management. Recently, botulinum toxin (BTX) type A has gained attention as an adjunct therapy for reducing excessive masticatory muscle activity. Objective: This report aims to describe the multidisciplinary management of a complex TMD case using 3D-printed stabilization splints combined with BTX type A injections. Case Report: A 24-year-old female presented with jaw pain and crepitation sounds upon mouth opening. She reported a history of bruxism and unilateral mastication. Cone-beam computed tomography (CBCT) revealed condylar erosion, osteophyte formation, and flattening. Clinical and radiographic findings confirmed myofascial pain and arthralgia with TMJ OA exacerbated by bruxism. Treatment included a custom 3D-printed stabilization splint and BTX type A injection into the masseter muscle. After 1 week, mouth opening improved from 34 mm to 35 mm, and to 38 mm after 1 month. The patient reported decreased pain during mastication and waking, along with reduced bruxism frequency. Conclusion: A multidisciplinary approach involving 3D-printed stabilization splints and BTX type A injections is effective in alleviating pain and improving function in complex TMD cases associated with bruxism. Keywords: Temporomandibular disorder, botulinum toxin, digital splint, bruxism